CARDIAC INVOLVEMENT IN PATIENTS SUFFERING FROM COVID-19 AND ITS ASSOCIATION WITH DISEASES SEVERITY AND PROGNOSIS - Raja, Waseem; Qayum, Uzma; Akhter, Naghmana; Samore, Naseer Ahmed; Tuyyab, Farhan; Waheed, Sidra; Nisar, Shazia; Fazal, Imran (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine frequency of cardiac involvement in patients of COVID-19. Secondary objective was to determine association of cardiac involvement with prognosis.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi Pakistan, from Apr to Jul 2020.Methodology: We prospectively assessed the laboratory data, Electrocardiogram and transthoracic echocardiography of all the COVID-19 patients admitted to our institute. Outcomes of interest included length of hospital stay, admission to Intensive Care Unit and mortality. Acute myocardial injury was defined by a value of high-sensitivity troponin I (hs-TnI) above the 99th percentile upper reference limit. Statistical Package for the Social Sciences (SPSS) version 23 was used for all the analysis.Results: Our study included 1015 patients, mean age 50.34 (SD 13.71) years, 887 (87.3%) males and 128 (12.6%) females. Three hundred and thirty (n=330, 32.5%) patients had evidence of acute cardiac injury as shown by raised cardiac troponins, but 50, 4.92% had left ventricle dysfunction. Raised cardiac enzymes were associated with marginally prolonged hospital stay (10.03 versus 9.32 days, p-value 0.07) and higher mortality (OR 2.634, confidence interval 1.252-5.543, p-value 0.01).Conclusion: Cardiac involvement is quite common among patients suffering from COVID-19 and predicts worse prognosis.